Structural and functional diversity of asparaginases: Overview and recommendations for a revised nomenclature - da Silva, Leonardo Schultz [UNESP]; Doonan, Liam B.; Pessoa, Adalberto; de Oliveira, Marcos Antonio [UNESP]; Long, Paul F. (Wiley, 2021)
Asparaginases (ASNases) are a large and structurally diverse group of enzymes ubiquitous amongst archaea, bacteria and eukaryotes, that catalyze hydrolysis of asparagine to aspartate and ammonia. Bacterial ASNases are important biopharmaceuticals for the treatment of acute lymphoblastic leukemia, although some patients experience adverse allergic side effects during treatment with these protein therapeutics. ASNases are currently divided into three families: plant-type ASNases, Rhizobium etli-type ASNases and bacterial-type ASNases. This system is outdated as both bacterial-type and plant-type families also include archaeal, bacterial and eukaryotic enzymes, each with their own distinct characteristics. Herein, phylogenetic studies allied to tertiary structural analyses are described with the aim of proposing a revised and more robust classification system that considers the biochemical diversity of ASNases. Accordingly, based on distinct peptide domains, phylogenetic data, structural analysis and functional characteristics, we recommend that ASNases now be divided into three new distinct classes containing subgroups according to structural and functional aspects. Using this new classification scheme, 25 ASNases were identified as candidates for future new lead discovery.
Keywords: biopharmaceuticals; bioprospecting; classification; enzyme diversity; l-asparaginase; phylogeny